2021
DOI: 10.1158/1055-9965.epi-20-0660
|View full text |Cite
|
Sign up to set email alerts
|

A Case–Control Study to Evaluate Environmental and Lifestyle Risk Factors for Esophageal Cancer in Tanzania

Abstract: Background: East Africa is affected by a disproportionately high burden of esophageal squamous cell carcinoma (ESCC). Methods: We conducted an incident case–control study in Dar es Salaam, Tanzania with 1:1 matching for gender and age. A questionnaire evaluated known and putative risk factors for ESCC. Cochran–Mantel–Haenszel and multivariable conditional logistic regression analyses were applied to evaluate associations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 45 publications
0
44
2
Order By: Relevance
“…For instance, smoking and drinking have been confirmed to be closely related to EC in many studies (7)(8)(9)(10). In China, heavy drinking and smoking are the main risk factors for EC (11), while in a Western study of ESCC, 80% of men and 40% of women had heavy drinking and smoking habits (12). A systematic analysis of 195 countries found that a large part of disability-adjusted life years caused by EC was attributable to smoking and drinking (13).…”
Section: Smoking and Drinkingmentioning
confidence: 98%
“…For instance, smoking and drinking have been confirmed to be closely related to EC in many studies (7)(8)(9)(10). In China, heavy drinking and smoking are the main risk factors for EC (11), while in a Western study of ESCC, 80% of men and 40% of women had heavy drinking and smoking habits (12). A systematic analysis of 195 countries found that a large part of disability-adjusted life years caused by EC was attributable to smoking and drinking (13).…”
Section: Smoking and Drinkingmentioning
confidence: 98%
“…To date ESCCAPE results have highlighted the role of alcohol, poor oral health and hot beverage consumption, [5][6][7] while other African studies have identified dietary factors (such as daily spicy chilies and salted foods) and indoor air pollution. 8 With a multicausal etiology, a hypothesized contributor to ESCC risk in East Africa is geophagia. Geophagy (also known as pica) is the intentional practice of eating earth or soil and is a habit that spans all continents of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies are the ESCC African PrEvention research (ESCCAPE) case‐control studies in Kenya, Tanzania and Malawi. To date ESCCAPE results have highlighted the role of alcohol, poor oral health and hot beverage consumption, 5‐7 while other African studies have identified dietary factors (such as daily spicy chilies and salted foods) and indoor air pollution 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from Asia, Europe, Latin America, Kenya, and Iran have reported associations of ESCC with poor oral hygiene, chronic periodontal disease, dental decay, and tooth loss (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Recently, three parallel case-control studies in Kenya and Tanzania, conducted as part of the African Esophageal Cancer Consortium (AfrECC) and ESCCAPE (esccape.iarc.fr) collaborations, reported possible associations of poor or infrequent oral hygiene with increased risk for ESCC in East Africa (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%